DIGITAL ASSET TAX: ARRANGEMENTS, IMPLEMENTATION, AND CHALLENGES - Gunawan Widjaja (Adisam Publisher, 2025)
Digital asset tax is an issue that is receiving increasing attention along with the rapid growth of blockchain technology and cryptocurrencies. Tax regulation on digital assets is essential to create transparency and accountability in the global digital market. Governments in various countries have begun to develop policies and regulations to govern, monitor, and ensure tax compliance of various forms of digital assets. However, the implementation of these policies poses various challenges, including the need for adequate technological infrastructure, international cooperation, and education for taxpayers. These challenges need to be addressed through a flexible and collaborative approach to ensure effective and sustainable implementation. Thus, the importance of comprehensive policy integration and awareness from all relevant parties for the successful implementation of digital asset tax.